Students’ Perceptions of Quality Across Four Course Development Models - Victoria S. Brown; David Lewis; Mario Toussaint (Online Learning, 2018)
Four course development models were used within a three-year time frame, allowing for an evaluation of the different models based upon students’ perceptions of the integration of the Quality Matters (QM) Standards, course structure, and quality. The study compared (a) faculty training, (b) instructional designer supported, (c) additional QM training course, and (d) no training or support used. Students were randomly selected from online courses from each of the categories to receive a survey to measure their perceptions about the courses. The students were asked about the design of the courses given the integration of the QM Standards, course structure, and quality. Significant results were found across all eight standards, course structure, and quality for the instructional-designer supported course model as compared with the other course design models.